2006
DOI: 10.1038/sj.onc.1209664
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of transendothelial migration of colon cancer cells by E-selectin-mediated activation of p38 and ERK MAP kinases

Abstract: The invasive properties of cancer cells depend on their intrinsic motile potential and on their ability to breach the endothelial barrier. In the present work, we investigated the mechanisms by which adhesion of colon cancer cells to E-selectin expressed by endothelial cells regulates the barrier function of these cells and modulates transmigration of cancer cells. We found that the stimulation of E-selectin by activating antibodies or the adhesion of HT-29 cells results in an increase in the activity of extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
119
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 54 publications
8
119
0
Order By: Relevance
“…p38 activation has apparently contradictory effects. In some cancer cells, it is involved in migration induced by IGF-II (29) and other factors (48,49). Indeed, IGF-II-induced migration was p38-dependent in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…p38 activation has apparently contradictory effects. In some cancer cells, it is involved in migration induced by IGF-II (29) and other factors (48,49). Indeed, IGF-II-induced migration was p38-dependent in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Except for inducing Tim-3 expression in endothelial cells as shown in this study, HMGB1 also up-regulates the expression of Eselectin in endothelial cells (4,25). E-selectin modulates transmigration of tumor cells by enhancing transendothelial permeability and migration of tumor cells (26)(27)(28). Thus, endothelial E-selectin and Tim-3 might synergize to benefit tumor metastasis by promoting migration and survival of tumor cells.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, E-selectin may contribute to initiation of metastasis in certain tissues, like liver, while having a limited role in lungs. In another set of studies, E-selectin was shown to contribute to transendothelial migration of tumor cells in vitro [42,43]. Tumor cell extravasation is considered to be an important step during lung colonization [10].…”
Section: Discussionmentioning
confidence: 99%